Model predictive current control with modified discrete space vector modulation for three-leg two-phase VSI - Jeong, Gi Heon; Lee, Hyung Woo; Yoon, Tae Yong; Park, Hyeon Jun; Lee, Kyo Beum (Journal of Power Electronics, 2023)
This paper proposes a model predictive current control (MPCC) method for a three-leg two-phase voltage source inverter to reduce the ripple of the output current. The proposed MPCC method is based on discrete space vector modulation, which is implemented by eliminating nonlinear modulation regions and generating virtual voltage vectors based on the stationary reference voltage vector axis. In addition, based on a voltage angle estimated using load parameters, the candidate voltage vectors in a specific region are generated, which reduces the calculation burden. Subsequently, the cost function is calculated using these candidate voltage vectors, and the optimal voltage vector selected using the proposed MPCC method is more accurate than the vector selected using the conventional MPCC method. Therefore, by applying the proposed method to increase the number of virtual voltage vectors, it is possible to obtain a delicate reference voltage. Consequently, the total harmonic distortion of the output current is reduced, resulting in an increase in power quality. The effectiveness and feasibility of the proposed method are verified through simulations and experiments.
Keywords: Current-control method; Deadbeat; Discrete space vector modulation; Model predictive; Model-predictive control; Output current; Predictive current control; Two phase; Two-phase VSI; Voltage vectors; Deadbeat; Discrete space vector modulation; Model predictive control; Predictive current control; Two-phase VSI